2023
DOI: 10.1007/s43678-023-00476-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of quality improvement methods to enhance implementation of a mental health care bundle in a pediatric emergency department

Abstract: Objectives We used quality improvement methods to implement a care bundle for children presenting to a pediatric emergency department (ED) with mental health concerns. A bundle novelty was that it included an option for assessment in a partnered clinic, not in the ED, to families of children assessed as having no medical or safety concerns. The primary aim of this study was to establish successful implementation of the bundle prior to studying its impact. Methods The bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This will increase patient"s knowledge, compliance to management plan, promote their self-efficacy to care for themselves, improve their QOL, and it could be reduce patient morbidity and mortality rates. (24) Significance of the study Epilepsy is a multifaceted neurological condition in developing countries. It was found that, in Egypt, the incidence rate of epilepsy was higher than that reported in New York, United State, and in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…This will increase patient"s knowledge, compliance to management plan, promote their self-efficacy to care for themselves, improve their QOL, and it could be reduce patient morbidity and mortality rates. (24) Significance of the study Epilepsy is a multifaceted neurological condition in developing countries. It was found that, in Egypt, the incidence rate of epilepsy was higher than that reported in New York, United State, and in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%